2018
DOI: 10.1371/journal.ppat.1007432
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 structural plasticity shapes HIV-1 phenotypic properties

Abstract: CCR5 plays immune functions and is the coreceptor for R5 HIV-1 strains. It exists in diverse conformations and oligomerization states. We interrogated the significance of the CCR5 structural diversity on HIV-1 infection. We show that envelope glycoproteins (gp120s) from different HIV-1 strains exhibit divergent binding levels to CCR5 on cell lines and primary cells, but not to CD4 or the CD4i monoclonal antibody E51. This owed to differential binding of the gp120s to different CCR5 populations, which exist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(79 citation statements)
references
References 111 publications
6
72
1
Order By: Relevance
“…Late X4 Envs were three-fold less sensitive to inhibition by sCD4 than early Envs (IC 50 = 56 vs 146 nM, P = 0.016). In contrast, early and late R5 Envs exhibited similar sensitivity to sCD4, in the range of that of the JR-CSF strain ( Fig 2D ), which is notoriously resistant to sCD4 [ 32 ]. Of note, the X4 Envs from patient #39 (red symbols in Fig 2C ) were unusually highly sensitive to sCD4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Late X4 Envs were three-fold less sensitive to inhibition by sCD4 than early Envs (IC 50 = 56 vs 146 nM, P = 0.016). In contrast, early and late R5 Envs exhibited similar sensitivity to sCD4, in the range of that of the JR-CSF strain ( Fig 2D ), which is notoriously resistant to sCD4 [ 32 ]. Of note, the X4 Envs from patient #39 (red symbols in Fig 2C ) were unusually highly sensitive to sCD4.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, SENS gp120s consistently bound more CXCR4 molecules than RES gp120s ( Fig 4A ). Similarly, we recently reported that distinct R5 gp120s can recognize different amounts of CCR5 [ 32 ], because they bind differentially to distinct conformations of the receptor, which exist in different quantities at the cell surface [ 32 ]. Monoclonal antibodies (mAbs) also showed divergent binding levels to CCR5 [ 47 ] or CXCR4 [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adding to the complexity, a recent study has highlighted that CCR5 exists in heterogeneous conformations and oligomerization states. Different subpopulations of CCR5 were preferred by divergent viruses (93) and importantly, macrophages and T cells expressed different subpopulations of CCR5 and it is likely another factor driving virus strains to be macrophage-tropic or T cell-tropic. It remains to be studied what subpopulations of CCR5 are expressed by all the various tissue myeloid cells that exist at the site of infection or if indeed this is the main determinant of M-tropism.…”
Section: Transfer Of Hiv To Cd4 T Cellsmentioning
confidence: 99%
“…CCR5 exists in diverse conformations and oligomerization states with different strains of HIV-1 binding differently to CCR5 molecules [4]. Binding assays of 35 S-labeled Env from different HIV-1 strains to activated CD4 + T cells has shown that Env recognizes different densities of CCR5 at the cell surface, with the number of CCR5 molecules recognized varying across cell types [4], such as T cells and macrophages.…”
mentioning
confidence: 99%
“…CCR5 exists in diverse conformations and oligomerization states with different strains of HIV-1 binding differently to CCR5 molecules [4]. Binding assays of 35 S-labeled Env from different HIV-1 strains to activated CD4 + T cells has shown that Env recognizes different densities of CCR5 at the cell surface, with the number of CCR5 molecules recognized varying across cell types [4], such as T cells and macrophages. Thus, imaging endogenously labeled CD4 and its coreceptors Glossary Bioluminescence resonance energy transfer (BRET): nonradiative phenomenon that occurs between a bioluminescence donor dipole and an acceptor dipole when both are situated at the right distance and orientation.…”
mentioning
confidence: 99%